Biological Invasion in the Era of Globalization - Sharma, Deepika (Prabandhan: Indian Journal of Management, 2015)
The objective of the article was to show how the diversity of the planet seems to get blurred due to the ongoing process of homogenization of flora and fauna on Earth. This was done by exploring the literature that provides a link between a globalized world and biological invasion. Though the literature on the subject is rather limited, but provides some insightful details into the matter. The article succeeded in showing that some of the innate tendencies of human behavior have actually made the problem of invasion worse. What remains to be investigated is the outcome of this continuous process of homogenization, whether it would lead to a complete destruction of diversity that the planet is known for, or whether the system would settle on a different equilibrium, where the term "native" would no longer hold relevance.